2018
DOI: 10.1681/asn.2017111205
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Antiporter LAT2/CD98hc with Uniporter TAT1 for Renal Reabsorption of Neutral Amino Acids

Abstract: Reabsorption of amino acids (AAs) across the renal proximal tubule is crucial for intracellular and whole organism AA homeostasis. Although the luminal transport step is well understood, with several diseases caused by dysregulation of this process, the basolateral transport step is not understood. In humans, only cationic aminoaciduria due to malfunction of the basolateral transporter yLAT1/CD98hc (SLC7A7/SLC3A2), which mediates the export of cationic AAs, has been described. Thus, the physiologic roles of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
(62 reference statements)
2
23
1
Order By: Relevance
“…We confirmed ablation of LAT2 transporter in CP on mRNA and protein levels (Additional file 1: Figure S2A, B) and measured amino acid levels in plasma and CSF samples. Previously Braun et al had reported elevated levels of 8 amino acids (Ala, Ser, Gly, Thr, Glu, Asp and Lys) for the serum of LAT2 knockout (KO) animals [37], however these alterations were not reproduced in our experiments using another LAT2 knock-out model (Additional file 2: Table S3) [32,33]. Therefore, we compared the CSF/ plasma ratio of each out of 19 detected amino acids [18 proteinogenic AA (all except Cys and Ile) and Tau] between wild type and LAT2 KO animals.…”
Section: Alterations In Csf Amino Acids Content Of Lat2 Knockout Animalscontrasting
confidence: 55%
See 2 more Smart Citations
“…We confirmed ablation of LAT2 transporter in CP on mRNA and protein levels (Additional file 1: Figure S2A, B) and measured amino acid levels in plasma and CSF samples. Previously Braun et al had reported elevated levels of 8 amino acids (Ala, Ser, Gly, Thr, Glu, Asp and Lys) for the serum of LAT2 knockout (KO) animals [37], however these alterations were not reproduced in our experiments using another LAT2 knock-out model (Additional file 2: Table S3) [32,33]. Therefore, we compared the CSF/ plasma ratio of each out of 19 detected amino acids [18 proteinogenic AA (all except Cys and Ile) and Tau] between wild type and LAT2 KO animals.…”
Section: Alterations In Csf Amino Acids Content Of Lat2 Knockout Animalscontrasting
confidence: 55%
“…Based on their mRNA expression level, their known transport function and our published experience with kidney proximal tubule epithelial amino acid transport, we postulate, that the antiporter y + LAT2 (Slc7a6) and the lower expressed (at mRNA level) antiporter y + LAT1 (Slc7a7) and the uniporters LAT4 (SLC43a2) and TAT1 (Slc16a10) play important roles ( Fig. 4) [32]. A limitation of our study and of our speculative transport schema shown in Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thereby, uniporters are also necessary for the net efflux of non-essential neutral and cationic amino acids (Rossier et al 1999;Meier et al 2002;Dave et al 2004;Bodoy et al 2005;Ramadan et al 2007;Guetg et al 2015; for reviews see Verrey, 2003;Poncet & Taylor, 2013;Broer & Broer, 2017). It has also been suggested that basolateral uniporters might quantitatively control overall basolateral amino acid efflux (Mariotta et al 2012;Guetg et al 2015;Vilches et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a homozygous mutation in SLC7A8 has been identified in a family with congenital cataracts [212]. The amino acid transporter TAT1 may have a modifying influence on the development of cataracts [212,213].…”
Section: Other Possible Inherited Conditions Related To Amino Acid Trmentioning
confidence: 99%